L6 Morbidity associated with primary hyperoxaluria type 1 (PH1) following liver transplantation: an aid for counselling of families. (12th September 2022) - Mbeledogu, Chukwudumebi; Hulton, Sally-Anne; Chikermane, Ashish; Gupte, Girish; Sharif, Khalid; Ong, Evelyn; Johansen, Lauren; Mourik, Indra Van; Kelgeri, Chayarani; Hartley, Jane
Abstract : Introduction: Primary Hyperoxaluria Type 1 (PH1) is a rare inherited metabolic disease frequently resulting in renal failure and multisystem deposition of oxalate. The current curative management is AGT enzyme replacement by liver transplantation with or followed by renal transplant when the systemic oxalate load has reduced. This review is focusses on identifying the morbidity associated with systemic oxalosis following liver transplant with an aim to aid counselling of families and inform clinicians. Patients and Methods: Twenty-nine patients with PH1 type 1 were cared for in our centre from 1998 to 2021. We are describing 8 patients with systemic oxalosis who had undergone a liver transplant at our centre followed by having or currently awaiting, sequential renal transplant. The patients physical and electronic notes were reviewed and complications identified by systematic enquiry. Results: Cardiovascular: Cardiovascular morbidity was significant and resulted in a delay of listing for renal transplantation in 2 patients. Vasoplegia developed in the immediate post-transplant period in 2 patients. Both required prolonged inotropic support. One of these patients developed ischaemic bowel and hepatic artery thrombosis resulted in liver failure in the acute post transplantation period requiring an urgent listing for a second liver transplant. A third patient developed right sided heart failure with diastolic dysfunction secondary to systemic oxalosis and had other manifestations of systemic oxalosis including growth failure requiring parenteral nutrition (PN), recurrent infections, pancytopenia and recurrent hypotension on dialysis and subsequently required palliative care for symptomatic management. Metabolic Disease 2 patients developed episodes of hyperammonemia following liver transplantation. One patient died due to complications of this and the other patient underwent a combined liver and kidney transplantation which led to a resolution. Eyes: 62.5% of patients had ophthalmology follow up and were found to have retinal oxalate deposition and pigmentation with no effect on visual acuity. Gastrointestinal system There were significant concerns about recurrent abdominal pain in at least 3 patients with 2 patients undergoing upper GI endoscopy, which yielded no significant findings. Two patients developed intestinal failure with PN dependency and hypoalbuminemia. In one of these patients, this led to long term feed intolerance. Bones: 5 patients had at least one pathological fracture. Long bone fractures were the most common type of fractures with 80% of patients having more than 1 pathological long bone fracture. Pancytopenia: Pancytopenia was also reported in 4 Patients with 75% of patients requiring a bone marrow aspirate which showed no cellular dysplasia but increased bone remodelling. Conclusion: PH1 is a rare but serious disease where liver transplant followed by renal transplant is the current model of care in our centre. Despite enzyme replacement with liver transplant, systemic oxalosis often continues to cause serious morbidity. For families undergoing transplantation, counselling regarding the liver transplant is essential but in addition, families should also be informed of the on-going effects of systemic oxalosis in the post-transplant period. Clinicians need a good understanding of the damaging effects of systemic oxalosis on multiple organs despite the efficacy of liver transplant in halting immediate production of oxalate.